2004
DOI: 10.1007/s00276-004-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variations of the hepatic arteries in 604 selective celiac and superior mesenteric angiographies

Abstract: In modern surgical and transplantation procedures the recognition of anatomic vascular abnormalities of the hepatic arteries is of greater importance than ever. The purpose of this study was to evaluate and classify these variations with respect to their impact on visceral surgery. A total of 604 selective celiac and superior mesenteric angiographies performed on patients with known or suspected liver cirrhosis or hepatic or pancreatic malignancies and on donors of partial liver grafts were analyzed retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
175
7
17

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(219 citation statements)
references
References 23 publications
20
175
7
17
Order By: Relevance
“…Among the 5 types with variations, the most common was the anomalous origin of the right hepatic artery arising from the superior mesenteric artery (10.6%), which was also found by Gruttadauria et al in 14.98% of the 701 cases studied [5] and Koops et al in 8.6% of the 604 angiograms that compose the study [9]. On the other hand, Koops et al found only 3% of left hepatic artery variations, while Hiatt et al and Gruttadauria et al found 9.7% and 11.5%, respectively [5,9,11]. An early bifurcation of the hepatic artery in right and left as direct branches of the celiac trunk was found in two cases in the study by Koops et al, but in only one of them the gastroduodenal artery originates from the left hepatic artery as presented on the current report [9].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Among the 5 types with variations, the most common was the anomalous origin of the right hepatic artery arising from the superior mesenteric artery (10.6%), which was also found by Gruttadauria et al in 14.98% of the 701 cases studied [5] and Koops et al in 8.6% of the 604 angiograms that compose the study [9]. On the other hand, Koops et al found only 3% of left hepatic artery variations, while Hiatt et al and Gruttadauria et al found 9.7% and 11.5%, respectively [5,9,11]. An early bifurcation of the hepatic artery in right and left as direct branches of the celiac trunk was found in two cases in the study by Koops et al, but in only one of them the gastroduodenal artery originates from the left hepatic artery as presented on the current report [9].…”
Section: Discussionmentioning
confidence: 52%
“…Hiatt et al, analyzed 1000 liver transplant patients and classified the hepatic vascularization into 6 types [11]. Among the 5 types with variations, the most common was the anomalous origin of the right hepatic artery arising from the superior mesenteric artery (10.6%), which was also found by Gruttadauria et al in 14.98% of the 701 cases studied [5] and Koops et al in 8.6% of the 604 angiograms that compose the study [9]. On the other hand, Koops et al found only 3% of left hepatic artery variations, while Hiatt et al and Gruttadauria et al found 9.7% and 11.5%, respectively [5,9,11].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, variations in the blood supply of the supramesocolonic organs have been frequently reported [6][7][8][9][10][11][12][13][14][15] . With the development of imaging technology, such as computed tomography (CT), magnetic resonance imaging (MRI), and angiography methods, information regarding vessel variation has become very important.…”
Section: Introductionmentioning
confidence: 99%